Characteristics of body building standard style dancers on the example of pair of world champions - Wiesława Pilewska; Patrycja Sech; Robert Pilewski (Nicolaus Copernicus University in Toruń, 2015)
Aim of the study The aim of the study was to determine the specificity of somatic build ballroom dancers sporting standard style. Materials The research material was sporting ballroom dancing couple having the highest international dance class "S". World Champions of 2013, the standard style. The length of the internship dance couples was 19 years. Subjects were trained from 6 to 7 days a week, after 3-4 hours a day. They were both 28 years. Methods Physical development assessment was based on anthropometric measurements of body weight and height, the length of the neck, upper and lower limbs, torso, thigh and lower leg, foot length, width, shoulders, pelvis, feet, chest, deep chest, circuits, waist, hips, thighs and ankles. Typological classification was also used to assess the specificity of physique subjects. Conclusions A pair of dance sport sporty style with a high level of standard sports (with the 2013 World Champions.) characterized by a specific construction of somatic manifested a certain size characteristics and indicators of body (shown in this work).Presented by their size parameters of somatic and morphological indicators should be considered as a result of the impact of dance training and the requirements of the standard style of discipline and separately for dancers and dance together for a couple as the specifics of their selection.